Learners’ schema in constructing meaning for figurative expressions used in the short story, “Qwertyuiop” / Royzal bin Tami - Tami, Royzal (2014)
A schema or schemata is a generalized system of knowledge for understanding concepts and its relationships with another, events, information and so on. Psychologists massively used the concept of schema theory in order to study the key importance of comprehension process. Rumelhart and Norman (1983) believe that schema can represent more information from a single sentence. Relatively, this study explores the use of background knowledge among L2 learners in constructing meaning of figurative expressions such as metaphor, personification and simile found from the short story „QWERTYUIOP‟. The three types of schema being identified are the linguistics, content and formal schema. A group of average L2 learners from the same class were the study‟s participants. They constructed meaning for 5 metaphors, similes and personifications through open-ended worksheets. They managed to construct meaning for the figurative expressions based on the three types of schema. There were also some similar traits in the way they constructed meaning based on each schema type. Factors such as background knowledge of the short story, the content knowledge, text reading, the text itself and participants‟ understanding were some of the influential factors that enabled meaning construction. All three types of schema are interrelated and shape the participants‟ comprehension to construct meaning. Keywords: Schema, Schema Theory, meaning, figurative expressions.